Student Care Strategy Through Application Code Of Ethics Of Santri In Pesantren Al-Qur’an Cijantung Ciamis - Saridudin (al-Afkar, Journal For Islamic Studies, 2023)
The pattern of parenting for santri in pesantren is quite varied, but there is no single parenting model that is said to be the most effective because each pesantren has different conditions. The purpose of this research is to see how the parenting model for Santri at Pesantren Al-Qur'an Cijantung Ciamis, the model of supervision, guidance, discipline, reward, and punishment in pesantren, and the implementation of the Santri Code of Ethics are carried out. This research is qualitative, with the main instrument being the researcher himself (a human instrument). This study uses data collection methods such as observation, interviews, and documentation. In data analysis techniques, using four stages, namely data reduction, data presentation, interpretation, and conclusion of data. The results of the study show that Pesantren Al-Qur'an Cijantung Ciamis, in caring for students, has a parenting system guided by the Santri Code of Ethics, which is carried out democratically. The code of ethics for students is the highest rule that must be obeyed by all students, including those who live in pesantren. The Code of Ethics is a standard of behavior and morals that must be obeyed by all students.